Positive Mood and the Perception of Variability Within and Between Groups - Stroessner, Steven J.; Mackie, Diane M.; Michalsen, Venezia (Group Processes & Intergroup Relations, 2005)
Three experiments investigated the effects of positive mood on perceptions of variability within and between groups. Participants formed impressions of two different and highly variable groups under a neutral or positive mood. When participants expected to learn about both groups, positive mood increased perceived intergroup similarity but did not affect perceived intragroup variability. In contrast, when participants expected to learn about only one group, judgments of intergroup and intragroup similarity were both affected by mood. Mood and the intergroup context influenced the nature and degree of information processing and resultant judgments of variability in social groups.
Keywords: dept.soc; peer-reviewed

Race, Ethnicity, and the American Urban Mainstream - Doob, Christopher Bates (Pearson/Allyn and Bacon, 2005)
"Race, Ethnicity, and the American Urban Mainstream uses history, biography, and sociological analysis to examine the achievements and struggles of racial and ethnic groups in American cities. This text is organized around social systems (politics, housing, education, economics, and work) rather than groups or concepts such as prejudice and discrimination. A group of in-depth profiles of minority communities, in cities such as Oakland, Detroit, Los Angeles, and Chicago, help to illustrate major concepts."--BOOK JACKET.
Keywords: Canada; United States; Ethnic relations; Ethnic relations; United States; Race relations; United States; Social conditions; Canada; Social conditions; Racism; United States; United States; City and town life; United States; Cultural pluralism; Urban minorities; dept.soc; faculty_collection

The racial wealth gap - Shapiro, Thomas M.; Kenty-Drane, Jessica L. (African Americans in the U.S. Economy, 2005)
Over the last several decades, academic discourse on racial inequality has focused primarily on political and social issues with significantly less attention on the complex interplay between race and economics. African Americans in the U.S. Economy represents a contribution to recent scholarship that seeks to lessen this imbalance. This book builds upon, and significantly extends, the principles, terminology, and methods of standard economics and black political economy. Influenced by path-breaking studies presented in several scholarly economic journals, this volume is designed to provide a political-economic analysis of the past and present economic status of African Americans. The chapters in this volume represent the work of some of the nation's most distinguished scholars on the various topics presented. The individual chapters cover several well-defined areas, including black employment and unemployment, labor market discrimination, black entrepreneurship, racial economic inequality, urban revitalization, and black economic development. The book is written in a style free of the technical jargon that characterizes most economics textbooks. While the book is methodologically sophisticated, it is accessible to a wide range of students and the general public and will appeal to academicians and practitioners alike.
Keywords: Social Science / Ethnic Studies / African American Studies; dept.soc

Stylistic sabotage and Thorstein Veblen's scientific irony - Cassano, G. (Journal of Economic Issues, 2005)
Keywords: dept.soc

Book Review: corrections: A comprehensive view - Ryan, Michael (Criminal Justice Review, 2005)
Keywords: book.review; dept.soc